Primary Study on Ureolysis-Based Microbially-Induced Calcium Carbonate Precipitation Technique for Geotechnical Applications - Tirkolaei, Hamed Khodadadi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Environmental concerns and application limitations of the conventional techniques for geotechnical engineering problems persuaded the geotechnical engineers to look for alternative solutions. In this regard, biogeotechnics which deals with bio-mediated and bio-inspired solutions to the challenges that vex geotechnical systems has been recently introduced. Within only around one decade of emerging this topic, it has received many attentions by researchers as it offers the promise of cost-effective, sustainable and non-disruptive solutions for a diversity of geotechnical applications. Microbially induced CaCO3 precipitation (MICP) is one the biological solutions, through which calcium carbonate is precipitated as binding agent between grains and/or filling materials within soil pores, by mediation of microorganisms. Successful development and implementation of the MICP technique for ground improvement would have wide application to many important geotechnical problems, such as increasing stiffness and shear strength to mitigate liquefaction potential; to enhance bearing capacity of soil beneath foundation and reduce associated settlements; to stabilize slopes; to facilitate excavation, boreholing and tunneling; to control erosion; and reducing permeability to reduce seepage of dikes and cut-off walls. Application of this technique may be especially useful underneath or near existing structures, where the application of conventional soil improvement techniques is restricted due to high cost or ground deformation associated with available technologies. There are several mechanisms for MICP. Ureolysis mechanism is the most concentrated one in the literature, in which ureolytic microorganisms are employed as biological mediators. Since introducing the ureolysis-based MICP into geotechnical engineering, many researches has been carried out on development and application of this technique into soil at laboratory scale. Although much success and progress have been attained by these studies, it was found that there is still lack of some geotechnical insights in biology-oriented side and some biological insights in geotechnics-oriented sides; for instance, no cheap, fast and geotechnical engineer-friendly method for estimation of precipitation progress was presented; and few attention has been also paid to the mineralogy of the precipitated calcium carbonate as it can influence mechanical properties of the treated soil and durability. In the present study, a hybrid of conductometry and precipitation mass measurement method in treatment solution (Biogrout) has been developed for monitoring the precipitation progress, which facilitates controlling over precipitation pattern, i.e. estimation on type, time, amount and place of precipitation within soil. It was found that the precipitation pattern in every treatment solution follows a logistic function, which was herein designated as microbial CaCO3 precipitation characteristics curve (MCPCC) since it represents three important characteristics (i.e. precipitation rate, precipitation ratio and lag duration). Effect of some significant influencing factors on these characteristics was investigated. Statistical models for precipitation rate and ratio were also presented. Potential type and morphology of the precipitates at different environmental conditions have been also assessed. It was observed that calcite as the most stable type of calcium carbonate does not always occur. Formation of non-stable phases can cause change in mechanical properties of treated soil as change in type and morphology of the precipitates during time was demonstrated in this study. Treatment of soil samples by using soaking and injection methods at high and low rate of precipitation were also separately evaluated. Different soil treatment methods were found to influence the mineralogy, shear wave velocity and unconfined compressive strength.

ÖZ: Çevre farkındalığının artışı ve konvansiyonel metodların limitasyonlarından dolayı geoteknik mühendisliği problemlerinin çözümü için alternatif yaklaşım arayışına girilmiştir. Bu çerçevede son yıllarda biyogeoteknik alanı, biyolojik veya biyolojiden esinlenen yaklaşımlarla geoteknik mühendisliği alanındaki sorunlara çözüm önermektedir. Son on yıl içerisinde oluşan ve gelişen bu yeni alan, çok yönlü geoteknik sorunların önlenebilmesinde ekonomik, sürdürülebilir ve çevre dostu çözümler sunmasından dolayı araştırmacılar tarafından, ilgi görmektedir. Mikrobiyolojik yöntemle mikro-organizmanın tetiklenmesi (indüksiyon) ile oluşan CaCO3 presipitasyonunun (MICP) tanecikleri bağlayıcı veya araları dolduran bir etkin madde olarak kullanılabilirliği çalışılmaktadır. Bu yöntemin başarılı bir şekilde geliştirilmesi ve zemin iyileştirmesinde uygulanabilir hale getirilmesi, zemin sıkılığının ve kayma mukavemetinin artırılması, sıvılaşma potansiyelinin iyileştirilmesi, zeminlerin taşıma gücünün artırılması, oturmaların azaltılması, şev stabilitesinin artırılması, kazı işlerinin kolaylaştırılması, tünel kazısının, erozyon kontrolünün yapılabilmesi, hidrolik iletkenliğin azaltılması gibi önemli geoteknik problemlerin çözümünde yararlı olacaktır. Özellikle konvansiyonel metodlarla iyileştirmeleri mümkün olmayan, pahalı veya deformasyonlara neden olabileceğinden, var olan binaların altında veya yanındaki zeminlerin iyileştirilmelerinde bu teknik çok kullanışlı olabilecektir. MICP’nin bir kaç yönteminden biri olan ve literatürde en yoğun çalışılan üreoliz yöntemi mikro organizmanın biyolojik bir aracı gibi çalıştırılmasıdır. Üreoliz kaynaklı MICP tekniğinin geoteknik mühendisliğinde uygulanabilirliği irdelenmeye başlandığından beri yöntemin geliştirilmesi ve zemine uygulanabilmesi için laboratuvar ölçeğinde çok sayıda araştırma yapılmıştır ve halen yapılmaktadır. Bu çalışmalarda belirli bir başarı elde edilmesine rağmen halen biyoloji kanadında geoteknik bilgisinin, geoteknik kanadında ise biyolojinin derinlemesine anlaşılamadığı gözlemlenmiştir. Dolayısıyla ucuz, süratli, ve kolay presipitasyon oluşumunun takip yöntemi geliştirilememiştir. Biyolojik yöntemle iyileştirilen zeminin mekanik davranış ve dayanıklılığını etkileyen kalsiyum karbonatın mineroloisi de yeterli çalışılmamıştır. Bu çalışma iyileştirme solüsyonu (Biogrout) içerisinde kondaktometri ve kütle presipitasyon ölçümü yöntemleri kullanılarak hibrid bir yöntemle, zemin içerisinde presipitasyon oluşumunu, gelişimini monitor ederek, zaman, miktar ve presipitasyon lokasyonlarının tesbitini içerir. Presipitasyon oluşumu ve dağılımının bir lojistik fonksiyon olan mikrobiyal CaCO3 karakteristik eğrisi (MCPCC) ile ifade edilebildiği ve üç önemli karakteristiği içerdiği izlenmiştir: presipitasyon hızı, presipitasyon oranı ve gecikme süresi. Bu çalışmada bazı önemli faktörlerin bu karakteristik unsurlara etkisi de araştırılmıştır. Presipitasyon hızı ve oranını ifade eden statistiki modeller sunularak, presipitasyonun potansiyel türü ve morfolojisi farklı çevresel faktörlerin etkisi altında değerlendirilmiştir. Sonuç olarak, en stabil kalsiyum karbonat türü olan kalsitin her zaman oluşmayabildiği gözlemlenmiştir. Ayrıca presipitasyonun türü ve morfolijisinde zaman içerisinde oluşan değişimin, iyileştirilmiş zeminin mekanik davranışında değişimlere neden olduğu da bu araştırma kapsamında irdelenmiştir. Sonuç olarak, en stabil kalsiyum karbonat türü olan kalsitin her zaman oluşmayabildiği gözlemlenmiştir. Ayrıca presipitasyonun türü ve morfolijisinde zaman içerisinde oluşan değişimin, iyileştirilmiş zeminin mekanik davranışında değişimlere neden olduğu da bu araştırma kapsamında irdelenmiştir.
Doctor of Philosophy in Civil Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2016. Supervisor: Asssoc. Prof. Dr. Huriye Bilsel.
Keywords: Soil Mechanics--Soils--Testing; Geotechnical Engineering; Biogeotechnics; Microbially-induced calcium carbonate precipitation; Biogrout; Ground improvement; Ureolysis; Civil Engineering